OPTIMIZING WASTE MANAGEMENT STRATEGIES FOR SUSTAINABLE CONSTRUCTION: ASSESSING THE IMPLEMENTATION OF CIRCULAR ECONOMY PRINCIPLES IN NIGERIA - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Jurnal Ilmiah Teknologi dan Rekayasa, 2024)
This study investigates waste management practices in Nigeria’s construction industry, with a focus on evaluating the adoption of circular economy (CE) principles. Using a mixed-methods approach, including structured surveys and semi-structured interviews with key stakeholders, the research highlights significant barriers to CE implementation. The findings reveal that while awareness of CE principles is moderately high, actual adoption remains limited due to financial constraints, weak regulatory enforcement, inadequate technical expertise, and insufficient infrastructure. The industry primarily relies on unsustainable waste disposal methods such as landfilling and open dumping, with limited recycling and material reuse. The study identifies opportunities for improving waste management through government-led financial incentives, regulatory reforms, capacity-building programs, and investment in recycling infrastructure. Furthermore, the adoption of digital tools like Building Information Modeling (BIM) and strategies such as modular construction are highlighted as promising approaches to reducing waste and enhancing resource efficiency. The research concludes with recommendations for a collaborative effort between government, industry, and educational institutions to drive the adoption of CE practices. Implementing these strategies could lead to significant environmental, economic, and social benefits for Nigeria’s construction industry.